OP0300-PARE Keele University – the Development of A Research User Group and A Structured System to Support Patient Involvement. (10th June 2014) - Rhodes, C.A.; Higginbottom, A.
Abstract : Background: The Arthritis Research UK Primary Care Centre at Keele University has run a dedicated Research User Group for 8 years. Members have been successfully recruited and supported to get involved in a variety of studies of musculoskeletal pain and arthritis. Objectives: We describe how the Research User Group has evolved and how members are supported to provide their perspective on living with musculoskeletal pain and arthritis, in both quantitative and qualitative research, through their involvement in different roles within cohort studies, randomised control trials and observations and interviews Methods: The group has now evolved from an original membership of 8 to over 60 members through a recruitment and selection based on "expertise by experience". Members then become part of subgroups specifically formed to align with the Centre's research strategy. Dedicated and paid staff, both with experience of living with a long-term condition, have been appointed to support the group. A set of guides has been produced and training workshops developed to help members to be involved in the different stages of the research cycle. Results: We now have 60 members involved in over 60 different projects. Members have coauthored publications [1], developed quality indicators to measure osteoarthritis care and produced a patient booklet to support osteoarthritis consultations [2] Conclusions: Our open model of recruitment has succeeded and a structured model of support has helped patient involvement become integral within our research projects. References: Grime J et al. Developing written information on osteoarthritis for patients. Health Expectations 2011. http://www.keele.ac.uk/media/keeleuniversity/ri/primarycare/pdfs/OA_Guidebook.pdf Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3635